Internet of Things and NodeMCU Devices to Enhance Laboratories Enabling Mycological Research in an Educational Context - Zárate-Moedano, Ramón; Contreras González, Rolando Rafael; Mendoza Cervantes, Guillermo; Suárez-Medellín, Jorge (International Journal of Online and Biomedical Engineering (iJOE), 2025)
Scientific experimentation is essential for both science education and the generation of new knowledge. However, many institutions face infrastructure limitations that hinder its implementation. This paper presents the design and development of an electronic system for conducting experiments to explore the effects of light conditions on fungal growth, based on physical computing technologies and the Internet of Things (IoT). The experimental platform consists of eight smart incubators, each equipped with sensors for critical environmental parameters such as temperature, humidity, CO2, and light intensity, managed by NodeMCU ESP8266 microcontrollers. The architecture operates on a local WiFi network and a central server using the IoT platform ThingsBoard, enabling real-time data collection and visualization in an educational context. The results demonstrate that the use of electronic and IoT devices facilitates scientific experimentation in both educational and research settings, while also promoting the development of technological competencies among students and teachers. This proposal shows that meaningful scientific research is achievable with accessible resources, contributing to comprehensive training in science and technology.